2019
DOI: 10.1093/annonc/mdz074
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fatigue and quality of life among epithelial ovarian cancer survivors: a GINECO case/control VIVROVAIRE I study

Abstract: Background: Few data are available on long-term fatigue (LTF) and quality of life (QoL) among epithelial ovarian cancer survivors (EOCS). In this case-control study, we compared LTF, symptoms and several QoL domains in EOCS relapse-free !3 years after first-line treatment and age-matched healthy women. Patients and methods: EOCS were recruited from 25 cooperative GINECO centers in France. Controls were randomly selected from the electoral rolls. All participants completed validated self-reported questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Furthermore, CIPN symptoms can present acutely, persist for years or even progress post‐therapy 3,14 . In severe cases, sensorimotor deficits may be irreversible 15 . Severe CIPN symptoms can interfere with activities of daily living such as writing, dressing and walking, significantly limiting quality of life 16 .…”
Section: Chemotherapy‐induced Peripheral Neuropathymentioning
confidence: 99%
“…Furthermore, CIPN symptoms can present acutely, persist for years or even progress post‐therapy 3,14 . In severe cases, sensorimotor deficits may be irreversible 15 . Severe CIPN symptoms can interfere with activities of daily living such as writing, dressing and walking, significantly limiting quality of life 16 .…”
Section: Chemotherapy‐induced Peripheral Neuropathymentioning
confidence: 99%
“…Despite significant advances in the treatment of gynecologic cancers, 1 patients with endometrial and ovarian cancers experience late effects from treatment 2 . Cancer‐related fatigue (CRF) is one of the most common and distressing symptoms reported 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have examined CRF in patients with early‐stage disease and common cancers 3,8 . A recent cross‐sectional study demonstrated that 20% of long‐term, relapse‐free survivors of ovarian cancer reported persistent CRF, and it was associated with high levels of depression, peripheral neuropathy, and sleep disturbance 2 . However, few researchers have examined CRF in patients with early‐ and late‐stage gynecologic cancers longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…In our present analysis, the younger patients with ovarian cancer were more affected by fatigue and sleep disturbance. The global QoL of women with ovarian cancer neutralizes after treatment to levels like those found in the normal population, but chronic fatigue, ovarian cancer-related symptoms, neurotoxicity, depression, and sleep disturbances persist as long-term side effects in cancer survivors [30].…”
Section: Discussionmentioning
confidence: 98%